Countering Disinformation: A Delicate Balance Between International Action and National Particularities - Flavia Durach; Mălina Ciocea; Cătălina Nastasiu (Media and Communication)
Policies to address disinformation aim to protect a number of key public goods, such as self-determination by citizens, fair elections, and a healthy media and information ecosystem. The literature on resilience to disinformation finds striking differences between states, resulting from particular combinations of factors. Consequently, there is a need to maintain a delicate balance between coordinated action at the global level and localized interventions in response to particular vulnerabilities. Starting from this premise, this article explores the complexities of local contexts that contribute to resilience and addresses the tensions in developing evidence-based policies grounded in a wider societal context and system of values. Our study relies on data collected in an EU-funded project, Strategic Planning to Strengthen the Disinformation Resilience and the Management of Hybrid Threats, implemented jointly by the Romanian Ministry of Foreign Affairs and the National University of Political Studies and Public Administration (Bucharest) between 2020 and 2023. By using insights from key project activities (public opinion survey and policy brief), we assess Romania’s needs and vulnerabilities, which can be addressed through personalized interventions for countering disinformation; we distinguish a particular architecture of policy responses and debate the possible courses of action for a systematic approach to disinformation. Overall, our study contributes to a better understanding of how effective policies for countering disinformation need to be fed by an awareness of relevant global and regional contexts as well as local factors, values, vulnerabilities, and sensibilities.